Floral resources in the surrounding landscape matrix augment plant species richness of bumblebee pollen loads in small, fragmented calcareous grasslands - Evan Taylor Sloan; Ira Hannappel; Annika L. Hass; Alexander Keller; Felipe Librán-Embid; Jelle Devalez; Elena Velado-Alonso; Triin Reitalu; Catrin Westphal; Hans Jacquemyn (Biological Conservation, 2025)

The Aegean Archipelago as cradle: divergence of the glaphyrid genus Pygopleurus and phylogeography of P. foina - Dimitrios N. Avtzis; Vasiliki Markoudi; Vangelis Mizerakis; Jelle Devalez; Georgios Nakas; Nikolaos Poulakakis; Theodora Petanidou (Systematics and Biodiversity, 2021)

Moderate fire severity is best for the diversity of most of the pollinator guilds in Mediterranean pine forests - Maria Lazarina; Jelle Devalez; Lazaros Neokosmidis; Stefanos P. Sgardelis; Athanasios S. Kallimanis; Thomas Tscheulin; Panagiotis Tsalkatis; Marina Kourtidou; Vangelis Mizerakis; Georgios Nakas; Palaiologos Palaiologou; Konstantinos Kalabokidis; et al. (Ecology, 2019)
Fire, a frequent disturbance in the Mediterranean, affects pollinator communities. We explored the response of major pollinator guilds to fire severity, across a fire‐severity gradient at different spatial scales. We show that the abundance of all pollinator groups responded to fire severity, and that bees and beetles showed in addition a significant species‐diversity response. Bees, sawflies, and wasps responded to fire severity at relatively small spatial scales (250–300 m), whereas flies and beetles responded at larger spatial scales. The response of bees, sawflies, and wasps was unimodal, as predicted by the intermediate disturbance hypothesis, whereas flies and beetles showed a negative response. A possible explanation is that the observed patterns (spatial scale and type of response) are driven by taxa‐specific ecological and life‐history traits, such as nesting preference and body size, as well as the availability of resources in the postfire landscape. Our observational study provides an insight into the effect of fire severity on pollinators. However, future research exploring the explicit link between the pre‐ and postfire landscape structure and pollinator traits and responses is required for further establishment and understanding of cause–effect relationships.

The effect of fire history in shaping diversity patterns of flower-visiting insects in post-fire Mediterranean pine forests - Maria Lazarina; Stefanos P. Sgardelis; Thomas Tscheulin; Jelle Devalez; Vangelis Mizerakis; Athanasios S. Kallimanis; Spyridon Papakonstantinou; Thanassis Kyriazis; Theodora Petanidou (Biodiversity and Conservation, 2017)